Tibetan diary : from birth to death and beyond in a Himalayan valley of Nepal - Childs, Geoff H., 1963- (University of California Press, 2004)
In this rich and deeply personal account of life in the highlands of Nepal, Geoff Childs chronicles the daily existence of a range of people, from venerated lamas to humble householders. Offering insights into the complex dynamics of the ethnically Tibetan enclave of Nubri, Childs provides a vivid and compelling portrait of the ebb and flow of life and death, of communal harmony and discord, and of personal conflicts and social resolutions. Part ethnography, part travelogue, and part biography, Tibetan Diary is a one-of-a-kind book that conveys the tangled intricacies of a Tibetan society. Childs's immensely readable and informative narrative incorporates contemporary observations as well as vignettes culled from first-person testaments including oral histories and autobiographies. Examining the tensions between cultural ideals and individual aspirations, he explores certain junctures in the course of life: how the desire to attain religious knowledge or to secure a caretaker in old age contrasts with social expectations and familial obligation, for example. The result is a vivid and unparalleled view of the quest for both spiritual meaning and mundane survival that typifies life in an unpredictable Himalayan environment.